The caged birds of Phnom Penh - Lipp, Frederick (Holiday House, 2001)
Ary, a young Cambodian girl, saves her money to buy a caged bird from the bird lady on which Ary makes a wish for her poor family's future and then sets free so it will carry her wishes into the open sky